KONSUMSI PANGAN DAN GIZI SERTA SKOR POLA PANGAN HARAPAN (PPH) PADA ANAK USIA SEKOLAH 7—12 TAHUN DI INDONESIA - Pertiwi, Karina Indah; Hardinsyah, Hardinsyah; Ekawidyani, Karina Rahmadia (Jurnal Gizi dan Pangan, 2014)
This study was aimed to assess food consumption, nutrient intake, Nutritional Dietary Quality (NDQ), Desirable Dietary Pattern (DDP) score, and correlation between DDP score and NDQ in school-age children 7—12 years old. The study was conducted by analyzing food consumption data of Basic Health Research 2010 collected through a 24-hour recall method. Subject obtained was 23,981 children. The results showed that most school-age children consume cereals (99.5%) and a few consume oily seeds (1.9%). Most school-age children (more than 50.0%) were deficit of energy, fat, carbohydrate, water, vitamin A, vitamin B1, vitamin B9, vitamin C, calcium, phosphor, and zinc. The mean of DDP score was 64.8±14.7. The mean of NDQ was 55.4±15.6. Statistical test results showed medium strong correlation between DDP score and NDQ (r=0.6).